Clostridioides difficile infections in Saudi Arabia: Where are we standing? - Najla A. Obaid; Abdullah A. Alhifany (Elsevier, 2020)
Clostridioides difficile infections (CDIs) are infamous healthcare-associated infections for causing watery diarrhea to long-term hospitalized patients with a high mortality rate. Epidemiological reports from western countries showed up-trending pattern in the number of CDIs cases. It is becoming immensely challenging for routine diagnostic protocols to detect CDIs accurately with short turnaround time. In Saudi Arabia, there is a paucity of data about CDIs' prevalence, recurrence rate, methods of screening and mortality rate. Nevertheless, a growing number of cases with similar virulence strains and comparable antibiotic resistance pattern to the western countries counterparts reported data were also detected. This review aims to present the status of CDIs' diagnosis and incidence rate in Saudi Arabia based on current literature.